Correlation between access to health information and health literacy among adolescents in Aceh, Indonesia - Chelsea Indriani; Dina Rasmita (Talenta Publisher, 2026)
The development of digital technology has brought about significant changes in how adolescents access health information; however, the main challenge remains their ability to evaluate and utilize information effectively. This study aims to examine the relationship between access to health information and levels of health literacy among adolescents in Aceh Tamiang. The study employs a descriptive correlational design with a quantitative approach, involving 88 students from SMA Negeri 4 Kejuruan Muda, selected via stratified random sampling. Data were collected via a health information access questionnaire and the Indonesian version of the Health Literacy Survey (Q16). Bivariate analysis using Spearman's Rho test revealed a very strong positive relationship between health information access and adolescents' health literacy levels (r = 0.802, p < 0.05). The majority of respondents had moderate access to information (60.2%), whilst health literacy levels were predominantly in the adequate category (43.2%); however, the majority of adolescents had inadequate literacy. This study indicates that good access to health information is a key factor in the development of health literacy in line with the European health literacy model. However, access to information without critical literacy skills risks increasing exposure to misinformation. These findings contribute to the development of comprehensive, context-specific health literacy interventions grounded in access to information and serve as a reference for the design of policies and health literacy education programs for adolescents in rural areas of Indonesia.